Dinámica Poblacional De Garrapatas En Ganado Bovino De Leche En Tres Fincas Del Municipio De Cajibio Cauca (2023)
The work was carried out in three farms located in the municipality of Cajibío, department of Cauca in the months of July, October and December of 2022. Where tick samples were taken from cattle, taking into account the rainy and dry season to see the degree of infestation and frequency of ticks with respect to humidity, precipitation and temperature and verify its incidence or decrease in the sampled cattle. For the analysis of the samples, a stereoscope was used with the collaboration of a specialist to identify the different species of ticks that infest cattle in the area, in addition to knowing the degree of infestation and the distribution according to temperature. humidity and rainfall in the area. According to the investigation carried out, the population consisted of 30 bovines distributed in 3 farms, choosing randomly 10 animals in each one. The visits were made on july, october and december of 2022. First of all, it determine the presence of Rhipicephalus sp, with 100% of the total samples. As a result, referring the degree of infestation in cattle; on farm 2, a high infestation was evidenced with 51.3%, with which it becomes pertinent to implement an adecuate management to avoid the proliferation of these ectoparasites. It was also recorded that for the rainy season (October-December) the frequency of ticks was higher, and the relative humidity and temperature had a significantly high positive linear relationship, which reflects the increase in the tick population on the farms.